Answer :

To prove:

tan 2A = tan (A + B + A – B)

We know that:

tan 2A =

tan 2A = {according to values given in question}

Hence, tan 2A =

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses